2015
DOI: 10.5465/amj.2012.1102
|View full text |Cite
|
Sign up to set email alerts
|

All Aspirations are not Created Equal: The Differential Effects of Historical and Social Aspirations on Acquisition Behavior

Abstract: Research on performance aspirations has tended to assume that historical and social aspirations work in parallel and influence strategic behavior in a similar manner. We posit that these two distinct modes of performance comparison in fact lead to dissimilar firm behavior. We also explore how variability in prior acquisition performance influences the relationship between aspiration levels and subsequent strategic behavior. We examine our questions in the context of mergers and acquisitions within the US comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(220 citation statements)
references
References 98 publications
10
192
1
Order By: Relevance
“…Other studies (e.g., Audia and Greve, ) assume that historical and social aspirations serve as independent constraints on decision making and hence calculate two separate indicators of performance‐aspirations comparisons. Still others (e.g., Baum et al, ; Kim, Finkelstein and Halebian, ) use historical and social performance feedback jointly to predict strategic decisions because dual comparisons may provide more information than would either comparison alone.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Other studies (e.g., Audia and Greve, ) assume that historical and social aspirations serve as independent constraints on decision making and hence calculate two separate indicators of performance‐aspirations comparisons. Still others (e.g., Baum et al, ; Kim, Finkelstein and Halebian, ) use historical and social performance feedback jointly to predict strategic decisions because dual comparisons may provide more information than would either comparison alone.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Building on this argument, the results of an emerging literature have revealed that decision makers' interpretation can strongly vary with the interpretative requirements of particular types of performance feedback (Greve & Gaba, ; Joseph & Gaba, ). For example, previous studies in this area showed that ambiguous feedback due to the presence of multiple aspiration levels or performance indicators is open to interpretation and thus affects a firm's problem‐solving behavior (Joseph & Gaba, ; Kim, Finkelstein, & Haleblian, ). In addition, other research demonstrated the important effects arising from the structural location of decision makers, such as the centralization or structural embeddedness of the executives (Gaba & Joseph, ; Joseph et al, ; Vissa, Greve, & Chen, ) in this context.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of studies have examined the role of performance relative to historical and/or social aspirations on risk taking. In this literature, managerial risk taking has been operationalized as acquisitions (Audia & Greve, 2006;Greve, 2008Greve, , 2011Iyer & Miller, 2008;Kim, Finkelstein, & Haleblian, 2015), entrance into new markets (Barreto, 2012), innovation (Chen, 2008;Chen & Miller, 2007;Gaba & Bhattacharya, 2012;Gaba & Joseph, 2013;Greve, 2003;O'Brien & David, 2014;Vissa, Greve, & Chen, 2010), illegal behavior (Baucus & Near, 1991;Harris & Bromiley, 2007;Madsen, 2013), and organizational change (Arrfelt, Wiseman, & Hult, 2013;Baum & Dahlin, 2007;Greve, 1998;Labianca, Fairbank, Andrevski, & Parzen, 2009;Lant, Milliken, & Batra, 1992;Massini, Lewin, & Greve, 2005;Park, 2007). Most of these studies have found evidence supporting BTOF main-effect predictions of greater managerial risk taking after underperforming and lower levels of risk taking when over performing.…”
Section: The Behavioral Theory Of the Firm And Prospect Theorymentioning
confidence: 99%
“…Historical and social comparisons, which determine reference points, have primarily been examined in isolation or in conjunction, while several studies have demonstrated that their effects differ. Chen (2008), Chen and Miller (2007) and Kim et al (2015) show that historical and social aspirations may have opposite effects, whereby risk taking increases when the firm's performance is above historical aspirations but decreases when performance is above social aspirations. Baum et al (2005) demonstrate that firms above social aspirations but below historical also tend to become more risk-taking.…”
Section: The Behavioral Theory Of the Firm And Prospect Theorymentioning
confidence: 99%